Designing Supplementary English Reading Material Based on Pos Bloc Medan - Br Sembiring, Yenita; br Butar-Butar, Gusty Bella Raskita; Lumbanbatu, Ira Maria Fran (Magister of English language Education study program, Universitas Muslim Nusantara Al Washliyah, 2024)
One of the causes of the lack of interest in reading is the lack of interesting reading materials. This study developed reading materials based on Pos Bloc Medan, a historic building in Medan, Indonesia that was transformed from a post office to a Pos Bloc. Creating new reading materials in the world of education is an important step to improve the quality of learning, expand access to knowledge, encourage innovation and creativity, and increase student engagement and motivation. This study aims to design new reading materials for students and college students to facilitate learning. The development technique used is descriptive qualitative and data collection is carried out by document analysis, observation and interviews. These findings provide important implications for the development of educational reading materials based on local culture in Indonesia